Formulation and Comparison of Glucomannan Metallocomplexes Made of Cobalt and Copper - Chandira, Rajappa Margret; Pethappachetty, Palanisamy; Venkatasubramaniam, Nagasubramanian; Samy, Dominic Antony (Asian Journal of Biological and Life Sciences)
The broad category of pharmaceutical science in which drugs are complex with metals like platinum, zinc iron, etc is defined as Metallopharmaceutics. The earliest work on Metallopharmaceutics is around 700 BC. In this work, Glucomannan, which is a plant-based drug, is used as a ligand to prepare anti-diabetic metal complexes of Cobalt and copper. Glucomannan is basically a polymer thought up of -(14)-linked D-mannose and D-glucose in a straight chain in a ratio of 8:5. Various pre-formulation studies were performed including swelling index and angle of repose for the pure drug only. The pre-formulation parameters inferred that the pure drug has fair flow properties with a swelling index of 81.8%. Formulations were analyzed spectrophotometrically using ATR-IR and UV-spectroscopy. In UV spectroscopy, it was analyzed that Glucomannan showed a distinct peak at 267 nm. Formulation of metal complexes was performed using the solvent-assisted method. The dissolution studies and release kinetics were performed for prepared Formulations (F1-F9). The Formulation F9 proved to be the best formulation following the Higuchi Diffusion plot with maximum linearity of 0.997. Thus, 500 mg Glucomannan + 1000 mg Cobalt (F9) had the sustained drug release throughout the dissolution period.
Keywords: Formulation; Glucomannan; Metallocomplex; Metallopharmaceutics; Release kinetics